2012
DOI: 10.1073/pnas.1117736109
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to apoptotic cells is regulated by indoleamine 2,3-dioxygenase

Abstract: Tolerance to self-antigens present in apoptotic cells is critical to maintain immune-homeostasis and prevent systemic autoimmunity. However, mechanisms that sustain self-tolerance are poorly understood. Here we show that systemic administration of apoptotic cells to mice induced splenic expression of the tryptophan catabolizing enzyme indoleamine 2,3-dioxygenase (IDO). IDO expression was confined to the splenic marginal zone and was abrogated by depletion of CD169 + cells. Pharmacologic inhibition of IDO skewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
213
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 174 publications
(226 citation statements)
references
References 38 publications
9
213
3
1
Order By: Relevance
“…CD300f-deficient mice developed a more severe autoimmune inflammation than the WT mice, when the mice were stressed with excess AC in the pristane-induced autoimmune disease model, which fits the fact that repeated exposure to AC leads to exacerbated disease in autoimmune-prone mice. 7,35,36 Moreover, our previous study showed that CD300f-deficient Fcgr2b −/− mice are predisposed to develop more severe splenomegaly and have a higher fatality rate than in Fcgr2b −/− mice. 29 Here we performed an in-depth analysis to identify cellular and molecular abnormalities behind this predisposition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CD300f-deficient mice developed a more severe autoimmune inflammation than the WT mice, when the mice were stressed with excess AC in the pristane-induced autoimmune disease model, which fits the fact that repeated exposure to AC leads to exacerbated disease in autoimmune-prone mice. 7,35,36 Moreover, our previous study showed that CD300f-deficient Fcgr2b −/− mice are predisposed to develop more severe splenomegaly and have a higher fatality rate than in Fcgr2b −/− mice. 29 Here we performed an in-depth analysis to identify cellular and molecular abnormalities behind this predisposition.…”
Section: Resultsmentioning
confidence: 99%
“…Although CD300f-deficient mice did not develop an overt immune phenotype, nor did they accumulate elevated levels of AC, we hypothesized that continuous exposure to AC could tip the balance towards autoimmunity, as repeated exposure to AC debris has been shown to exacerbate disease in autoimmune-prone mice, but not in normal mice. 7,35,36 Therefore, we injected AC into WT and CD300f-deficient mice, in the presence of pristane, an alkane that induces a SLE-like disease by promoting the release of auto-antigens from AC. 37,38 Although pristane alone did not cause any difference in splenomegaly between Cd300f +/+ and Cd300f CD300f deficiency causes an accelerated autoimmune response in Fcgr2b −/− mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, we have reported that apoptotic cells drive rapid expression of the tryptophan (Trp)-metabolizing enzyme indoleamine 2,3 dioxygenase 1 (IDO1) in MARCO + marginal zone (MZ) MΦs that is critical for prevention of apoptotic cell-driven autoimmunity (6). Moreover, studies by our group (6) and Sharma et al (9) have shown a link between a loss of IDO1 activity and exaggeration of autoimmune pathology in MRL lpr/lpr mice.…”
mentioning
confidence: 98%
“…Macrophages (MΦ) are key drivers of the early innate response to apoptotic cells (4,5), and recent work has shown that tissue-resident MΦs are responsible for initial IL-10 production, promoting regulatory adaptive immunity to apoptotic cell antigens and prevention of inflammatory autoimmunity (4,6,7).…”
mentioning
confidence: 99%